The Influence of Adaptive Leadership, Psychological Safety, and Knowledge Sharing on the Innovative Performance of Health Workers in Hospitals - Fahmi Agoes, Izzra; Farhan Indrajianto, Mohamad; Ulya, Nasyidatul; Clarista, Sella; Bernarto, Innocentius (Jurnal Indonesia Sosial Sains, 2026)
This study aims to analyze the influence of adaptive leadership, psychological safety, and knowledge sharing on the innovative performance of health workers in hospitals. The approach used is quantitative with a cross-sectional design. Data was collected through a questionnaire distributed to 280 selected respondents using purposive sampling techniques. Data analysis was carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to examine the relationships between variables in the research model. The results show that adaptive leadership, psychological safety, and knowledge sharing have a positive and significant effect on innovative performance. Among the three variables, knowledge sharing had the strongest influence, followed by psychological security and adaptive leadership. In addition, the high R-squared value indicates that the model has strong predictive ability in explaining innovative performance variations. The IPMA analysis also shows that knowledge sharing is the most important factor to improve efforts to encourage innovative performance of health workers. The conclusion of this study is that the innovative performance improvement of health workers can be achieved through strengthening knowledge sharing practices, supported by a work environment that fosters high psychological safety and adaptive leadership. The implications of this study emphasize the important role of hospital management in creating a culture of knowledge sharing and a psychologically safe work environment to encourage sustainable innovation.